2017
DOI: 10.1063/1.4991970
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensing of gas molecules by a 99.9% semiconducting carbon nanotube-based field-effect transistor sensor

Abstract: Carbon nanotubes (CNTs) have been regarded as a promising material for highly sensitive gas sensors due to their excellent material properties combined with their one-dimensional structural advantages, i.e., a high surface-to-volume ratio. Here we demonstrate a CNT-based gas sensor based on assembling highly purified, solution-processed 99.9% semiconducting CNT networks bridged by palladium source/drain electrodes in a field-effect transistor (FET) configuration with a local back-gate electrode. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…42 Nevertheless, it is important to highlight that adopting the inverter conguration slightly hinders the sensitivity of the device in comparison to our previously reported single SWCNTs-FET devices. 42 However, the LOD for the inverted device is still reasonably comparable to other SWCNT-FET based gas sensors 21,24,26,[48][49][50][51][52] (see Table S4 in the ESI †). Moreover, the inverter conguration enables simpler data measurement and analysis, a possible miniaturization of the complete measurement chain of the sensor, and low power consumption.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…42 Nevertheless, it is important to highlight that adopting the inverter conguration slightly hinders the sensitivity of the device in comparison to our previously reported single SWCNTs-FET devices. 42 However, the LOD for the inverted device is still reasonably comparable to other SWCNT-FET based gas sensors 21,24,26,[48][49][50][51][52] (see Table S4 in the ESI †). Moreover, the inverter conguration enables simpler data measurement and analysis, a possible miniaturization of the complete measurement chain of the sensor, and low power consumption.…”
Section: Resultssupporting
confidence: 61%
“…[12][13][14][15][16][17][18][19] Usually, these gas sensors are in the form of SWCNT-FET devices and are based on gas exposuretriggered modications of the SWCNT electrical response. 15,17,[20][21][22][23][24][25][26] The reactivity of pristine SWCNTs (i.e. non-functionalized SWCNTs) is usually described by two different phenomena: a modication of the height of the Schottky barrier at the SWCNT/electrode junction, or a doping of the SWCNT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MWCNTs lack carbon band gaps or have narrow band gaps; the tube is mainly metallic so that the adsorption of the chemical molecules has little effect on the electrical conductivity. Therefore, the conductivity of the MWCNTs is not as sensitive as that of SWCNTs, but it has been shown that the MWCNTs still have excellent sensing characteristics to substances such as water vapor [ 21 ], NH 3 [ 22 , 23 ], NO 2 [ 18 ], and O 2 [ 24 , 25 ].…”
Section: Configuration and Sensing Mechanismmentioning
confidence: 99%
“…Excellent progress has been made in CNT‐based chemical and biological sensors, and these areas have already been the topic of several reviews . Of particular interest in this review is the application of sorted SWCNTs for a comprehensive range of sensing technologies …”
Section: Transistorsmentioning
confidence: 99%